Health Counselling on Coping With Stress And Making Peace with Diabetes Mellitus in Coastal Areas of South Kalimantan - Tutpai, Gertudis; Unja, Ermeisi Er; Ayu, Maria Frani (Journal of Digital Community Services, 2025)
One of the non-communicable diseases (NCDs), which causes the most serious threat to health in the world is diabetes mellitus. Data from the Tanah Laut District Health Office shows that the prevalence of type II DM in 2023 will increase to 5053 people. Based on these results, it is considered necessary to make an effort to prevent Diabetes Mellitus by providing counselling on how to prevent and control diabetes mellitus. The method of community service carried out is to conduct educational and participatory counselling with pre and post tests.This community service activity was carried out on Wednesday 18 December 2023 in the Takisung Health Centre work area, Tanah Laut Regency. The results obtained were that there was an increase in community knowledge about stress management and diet in patients with diabetes mellitus in the Takisung area, Tanah Laut.   People who previously did not know that stress can also be one of the things that can trigger an increase in blood sugar in diabetes mellitus patients, after counselling they know many things that can cause diabetes mellitus. The community also understands how to deal with stress and prevent stress from occurring. It is hoped that health centre staff can carry out routine counselling activities in the Takisung area to control the incidence of Diabetes mellitus.